COMPOUND ENGLISH ANATOMICAL TERMS AND THEIR LATIN EQUIVALENTS IN THE TEXTBOOK HUMAN ANATOMY (VOL. I) - Nijolė Litevkienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The article presents the analysis of compound English and Latin anatomical terms and the analysis of their specific configurations. The oldest language that played a very important role in the development of medicine in Europe was Greek. English medical terminology developed from medieval Latin terminology, which had absorbed a developed Greek terminology. Modern anatomical terminology is based on centuries-old tradition and constantly revised knowledge. Most anatomical and clinical terms used in medicine today are Latin or Latinized Greek words, the origin of which can be traced back to the 5th century B.C. In the textbook “Human Anatomy”, M. Prives, V. Bushkovich, and N. Lisenkov offer a progressive view of descriptive, evolutionary, functional, and practical anatomy. Medical terms in the textbook can be basically divided into one-word and multiple-word terms. Anatomical terminology is the foundation of medical terminology, so it is extremely important for physicians and scientists worldwide to use uniform terms for each anatomical entity. Medical terms in the textbook can be basically divided into one-word and multiple-word terms. One-word terms can be simple (underived) words, derived words, compounds, or a combination of derived and compound words. Compound anatomical terms can consist of two-five words. This article focuses on the comparative structural and semantic analysis of the anatomical terms of Latin and English languages. The study reveals some significant coincidences and differences between two-word and three-word Latin and English anatomical terms and their frequency of usage. One of the terminologies of the fields of medical science is analysed using descriptive and comparative methods. A descriptive-analytical method was employed to perform quantitative and qualitative (of specific configurations) analyses.